2006
DOI: 10.1242/jcs.03061
|View full text |Cite
|
Sign up to set email alerts
|

Brain-specific BNIP-2-homology protein Caytaxin relocalises glutaminase to neurite terminals and reduces glutamate levels

Abstract: Human Cayman ataxia and mouse or rat dystonia are linked to mutations in the genes ATCAY (Atcay) that encode BNIP-H or Caytaxin, a brain-specific member of the BNIP-2 family. To explore its possible role(s) in neuronal function, we used protein precipitation and matrix-assisted laser desorption/ionisation mass spectrometry and identified kidney-type glutaminase (KGA) as a novel partner of BNIP-H. KGA converts glutamine to glutamate, which could serve as an important source of neurotransmitter. Co-immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 55 publications
0
71
0
Order By: Relevance
“…Furthermore, the BCH domain of BPGAP1, a close homolog of Cdc42GAP/p50RhoGAP, also promotes Cdc42-dependent short pseudopodia, which are necessary for cell migration (Shang et al, 2003;Lua and Low, 2004) and Ras/MAPK activation (Lua and Low, 2005). More recently, we demonstrated that the BCH domain of the brain-specific BNIP-H/Caytaxin is involved in glutamate production and glutaminase trafficking (Buschdorf et al, 2006). These findings suggest that the BCH domain exerts an additional regulatory control over the cellular activity of their cognate small GTPases or other specific proteins.…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, the BCH domain of BPGAP1, a close homolog of Cdc42GAP/p50RhoGAP, also promotes Cdc42-dependent short pseudopodia, which are necessary for cell migration (Shang et al, 2003;Lua and Low, 2004) and Ras/MAPK activation (Lua and Low, 2005). More recently, we demonstrated that the BCH domain of the brain-specific BNIP-H/Caytaxin is involved in glutamate production and glutaminase trafficking (Buschdorf et al, 2006). These findings suggest that the BCH domain exerts an additional regulatory control over the cellular activity of their cognate small GTPases or other specific proteins.…”
Section: Introductionmentioning
confidence: 90%
“…Other proteins isolated several times were RNA polymerase II polypeptide G (four clones) and Bcl-2-associated transcription factor (two clones). Considering the nuclear localization of these two proteins, it seemed implausible that they were interacting partners for caytaxin, which is a cytoplasmic protein (Buschdorf et al, 2006;Hayakawa et al, 2007). Another 17 genes were isolated only once.…”
Section: Binding Of Caytaxin To Kinesin Light Chainsmentioning
confidence: 99%
“…So far, no biological activities have been assigned to the Nterminal regions of caytaxin, BNIP-2 and BNIP-S (Buschdorf et al, 2006;Qin et al, 2003;Zhou et al, 2005;Zhou et al, 2006). However, if the binding of caytaxin to KLCs has physiological significance, overexpression of the caytaxin N-terminal fragment might exert dominant-negative effects on the endogenous caytaxin.…”
Section: Effects Of Caytaxin On Extension Of Neuritesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported that caytaxin plays an important role in axonal transporting [65], glutamate synthesis [66], synaptic apoptosis, and neurodegenerative diseases [67]. By using coimmunoprecipitation and mass spectrum detection, our unpublished preliminary results showed that DAPK1 could also interact and phosphorylate caytaxin on serine 46 at the presynaptic area in the mice model of middle cerebral artery occlusion (MCAO).…”
Section: Dapk1 and Caytaxinmentioning
confidence: 84%